2020
DOI: 10.1155/2020/8844730
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of MSC-Derived Exosomes in Tumor Development

Abstract: Mesenchymal stem cells (MSCs) are a class of adult stem cells derived from the mesoderm. They can self-renew, have multidirectional differentiation potential, and can differentiate into a variety of mesenchymal tissues. MSCs can produce a large number of exosomes, which can mediate information exchange and transmission between cells in the tumor microenvironment under conditions of rest or stress. Recent studies have reported conflicting findings regarding the effect of MSC-derived exosomes on tumors. Some stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 89 publications
0
34
0
Order By: Relevance
“…Exosomes exceed MSCs in sustainability and scalability as they are more stable than MSCs [ 25 , 78 ]. However, their tumorigenic potential is debatable, as some studies support their tumor promotion potential, whereas others support their tumor inhibitory potential [ 79 ]. Preclinical and clinical studies have demonstrated the effects of exosomes in reducing cytokine storm complications, such as alveolar inflammation, edema, and epithelial tissue regeneration in inflammatory diseases, such as ARDS, asthma, COPD, and acute lung injury (ALI) [ 25 , 80 86 ].…”
Section: Msc-derived Exosomes and Covid-19mentioning
confidence: 99%
“…Exosomes exceed MSCs in sustainability and scalability as they are more stable than MSCs [ 25 , 78 ]. However, their tumorigenic potential is debatable, as some studies support their tumor promotion potential, whereas others support their tumor inhibitory potential [ 79 ]. Preclinical and clinical studies have demonstrated the effects of exosomes in reducing cytokine storm complications, such as alveolar inflammation, edema, and epithelial tissue regeneration in inflammatory diseases, such as ARDS, asthma, COPD, and acute lung injury (ALI) [ 25 , 80 86 ].…”
Section: Msc-derived Exosomes and Covid-19mentioning
confidence: 99%
“…Although MSCs are expected to be developed as drug delivery vehicles, several studies have reported that MSCs support the construction of the tumor microenvironment by differentiation into cancer (carcinoma-, tumor-)-associated fibroblasts (CAFs) [23,68], as well as accelerate tumor growth and metastasis by stimulating tumor cells via direct cell-cell interactions and tumor cell-derived extracellular vesicles (EVs) [68][69][70][71]. CAFs closely resemble myofibroblasts and express α-smooth muscle actin (α-SMA) and fibroblast activation protein (FAP) [72].…”
Section: Differentiation Capacity Of Mscs To Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Several studies have suggested that EVs secreted from MSCs in tumor tissues promote tumor growth and metastasis. It has been reported that microRNA-15a, 21, 34a, 191, 125a, 140, and 222/223 in MSC-derived EVs improved the resistance to anti-cancer drugs, proliferation, migration of cancer cells, and angiogenesis by tumor stromal cells [69]. However, studies have also reported that MSCderived EVs possess anti-tumor effects [69].…”
Section: Influence Of Msc-derived Evs On Tumor Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC can upregulate tumour PD-L1 [ 151 ] and are important tumour microenvironment regulators [ 152 ]. MSC can self-renew, have a multidirectional differentiation potential, and efflux large quantities of exosomes, thereby potentially acting as a hub to integrate and influence signals across the tumour microenvironment [ 153 ]. MSC can release mitochondria, both directly and within extracellular vesicles, which can be taken up by other cells, which may be a treatment target [ 154 ].…”
Section: Wider Regulators Of the Tumour Microenvironment And Immunmentioning
confidence: 99%